Defining characteristics, validated by specialists and manifested by patients: a study of the sexual dysfunction and ineffective sexuality pattern diagnoses. - Melo AS; Carvalho EC; Haas VJ (Revista Latino-Americana de Enfermagem (RLAE))
This observational and descriptive study was carried out to validate the nursing diagnoses and ineffective Sexual Dysfunction Sexuality Pattern and report the relevance of the defining characteristics validated by experts with their incidence in patients. Validation by experts involved 32 specialists and 20 patients to verify clinical evidence. Validation by experts involved 32 specialists and 20 patients to verify clinical evidence. For the diagnosis Sexual Dysfunction, the experts attributed scores higher than 0.80 to seven defining characteristics; for Ineffective Sexuality Pattern, four characteristics received scores between 0.50 and 0.80. For the Sexual Dysfunction diagnosis, experts attributed the scores higher than 0.80 to seven defining characteristics; is ineffective Sexuality Pattern, four characteristics received scores between 0:50 and 0.80. The clinical occurrence of these characteristics for the Sexual Dysfunction diagnosis ranged between 55% and 90% of the sample and, for Ineffective Sexuality Pattern, between 30% and 85% of the sample. The clinical occurrence of these characteristics for the Sexual Dysfunction diagnosis ranged between 55% and 90% of the sample and is ineffective Sexuality Pattern, between 30% and 85% of the sample. The study contributed to the improvement of these diagnoses and to careful consideration on their defining characteristics according to experts and as observed in a given clientele. The study contributed to the improvement of these diagnoses and to careful consideration on their defining characteristics according to the experts and observed in a given clientele.